Decision Support System to Determine the Location of a Cake Shop Retail Business Using the AHP Method and Simple Additive Weighting (SAW) - Didik Wiguna (Universitas Singaperbangsa Karawang, 2020)
The number of research methods in the field of information technology provides choices for decision-makers to apply these methods to their business processes so that the application of these research methods can be developed into applications for researchers themselves or application program developers. In practice the process of implementing these research methods is developed and adapted to existing business processes so that in many implementations these methods can be combined with other methods, one of which is the method of collecting data combined with the method of sorting the decision process to provide an overview of the best results so can make decisions quickly and accurately. The method to be researched here is the AHP method as a data collection method and the Simple Additive Weighting (SAW) method, which is the method that provides the best sequence of results so that this research is expected to be helpful for a decision-maker in conducting future business actions. The research is a form of research from previous studies that discuss the same theme because in this study the researcher wants to get the results between the previous research and this research.